2022
DOI: 10.18280/i2m.210504
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Automation of Temperature Control Based on Mobile Application Technology (MAT) for Precision Oyster Mushroom Cultivation

Abstract: Oyster mushrooms can usually be found in the forest and grow on rotten logs with temperatures ranging from 21-28℃. The farmers are used the feeling method to measure the range of air temperature in the oyster mushroom cultivation area so that faced the difficulty for controlling the temperature conventionally. This research describes an intelligent device to regulate the air temperature automatically using Peltier TEC-1 12706, which was assisted with ice cubes and aluminum water blocks as cool temperatures aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Technological advancements over the years have led to the integration of numerous Internet of Things (IoT) technologies, resulting in more advanced and sophisticated systems such as online monitoring [1][2][3][4] embedded hardware-software [5][6][7][8] and intelligent system [9][10][11]. As has been noted, the increasing prominence of these IoT technologies provides greater advantages to enhance the efficacy of conventional processes or approaches; as a result, these technologies have been extensively investigated and deployed in various sectors, including the food and agriculture industry, including bee farming.…”
Section: Introductionmentioning
confidence: 99%
“…Technological advancements over the years have led to the integration of numerous Internet of Things (IoT) technologies, resulting in more advanced and sophisticated systems such as online monitoring [1][2][3][4] embedded hardware-software [5][6][7][8] and intelligent system [9][10][11]. As has been noted, the increasing prominence of these IoT technologies provides greater advantages to enhance the efficacy of conventional processes or approaches; as a result, these technologies have been extensively investigated and deployed in various sectors, including the food and agriculture industry, including bee farming.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, it was concluded that the environmental aspects that need to be considered in oyster mushroom cultivation are temperature, humidity, and light intensity. In general, a good temperature for the development of oyster mushrooms is between 23 ℃ to 28 ℃ while the air humidity is between 70% to 90% (Yudhana, Akbar, Mufandi, & Larombia, 2022) (Sihombing, Astuti, Herriyance, & Sitompul, 2018). The light intensity required for the growth of oyster mushrooms is ±300 Lux (Firmansyah, et al, 2022), (Mohammed, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%